Penyuluhan Tentang Manajemen Nyeri Dengan Analgetik Narkotik Pada Pasien Pasca Anestesi Umum - Nawawi, Achmad (Yayasan Inspirasi El Burhani, 2024)
Introduction: Pain is a form of sensory and emotional experience that is not unpleasant sensations associated with tissue damage or likely to occur tissue damage. Surgery or surgery is an invasive treatment action through incisions to open or display the part of the body to be dealt with and end with wound closure and suturing. With this surgery a person will experience pain both before and after surgery. One way to treat pain is using Post-surgical pain management techniques using pharmacological therapy. Opioids are a group of drugs that have properties like opium or morphine Objective: Service Activities to the Community (PKM) aims to help increase knowledge about the effects side effects of narcotic analgesics Method: This PKM is carried out by providing counseling education using leaflets and audio visuals for preoperative patients using general techniques anesthesia as many as 30 respondents. Result: level of knowledge about pain management with narcotic analgesics in patients after general anesthesia in the good category before administration education by 17%, Sufficient by 47%, Less by 37%, After providing education increased by 100%. Conclusion: After providing education, the respondent's level of knowledge increased by 100%.